Penerapan Trias Politika di Indonesia dalam Tinjauan Fikih Siyāsah - Rahmat Rahmat; Indah Baharilla (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to understand the concept of siyᾱsah jurisprudence, to find out the application of the trias politica in Indonesia, and to find out the review of siyᾱsah jurisprudence regarding the application of the trias politica in Indonesia. This research is qualitative research, which means the data used in the research is qualitative data. Qualitative data includes data in the form of sentences in the form of statements and certain indices except numbers. Meanwhile, the form of research is library research. The results of this research found that the concept of siyᾱsah fiqh is to form a political system of government in a daulah that is based on Islamic law with complete and systematic components in order to achieve the goals of the law. Indonesia, in its system of sharing state power, tends to follow the concept of trias politica put forward by Montesquieu, but the application of this concept is not stated explicitly. The application of the trias politica in Indonesia, which is stated in the 1945 Constitution, is justified by the siyᾱsah fiqh. Because the same concept is also applied by Islamic politics, even though in essence, since its inception, Indonesia was not a country based on Islamic law but contained Islamic values.